The effect of mouthrinses containing zinc and triclosan on plaque accumulation and development of gingivitis in a 3-week clinical test - Schaeken, M J; van der Hoeven, J S; Saxton, C A; Cummins, D (Journal of clinical periodontology, 1994)
Experimental mouthrinses containing 0.4% zinc sulphate and 0.15% triclosan were compared with a chlorhexidine and a negative control mouthrinse in a 3-week clinical trial. The zinc/triclosan mouthrinses 1 and 2 differed in their ethanol and humectant contents used to deliver the triclosan. The experimental protocol employed the partial mouth gingivitis design, whereby participants wear a toothshield during toothbrushing. Gingival health at baseline was established by professional cleaning, oral hygiene instruction and effective toothbrushing 3 x per day during a pre-experimental period of 2 weeks. The mouthrinses were subsequently used 2x daily following normal toothbrushing during 3 weeks. The pre-experimental oral hygiene phase very effectively reduced plaque levels and gingival bleeding. During the rinsing period, in the absence of mechanical removal of plaque from the protected teeth, gingival bleeding rose to above the prestudy level in the negative control group. The increments (change from baseline to 21 days) of plaque and bleeding scores for the zinc/triclosan mouthrinse 1 were significantly lower than those in the negative control group. As expected, plaque and gingivitis scores were lowest in the group that rinsed with chlorhexidine. The results extend previous observations on the efficacy of the zinc/triclosan system to maintain gingival health.